Jihad Dalam Bingkai Multikulturalisme Perspektif Pendidikan Islam Di Papua Barat Daya - M., Fardan Abdillah (Al-Riwayah : Jurnal Kependidikan, 2024)
The objectives of this research are determine the perception of Jihad within the frame of Multiculturalism for the people of Southwest Papua. The dedication method used is quantitative. The data collection procedures are the application of teaching methods, interviews, observation and documentation. Then, in collecting data using analysis instruments on the results of applying the method, data analysis is quantitative/statistical in nature which aims to test the hypotheses that have been set. According to several figures in Southwest Papua, the perception of jihad in the frame of multiculturalism is: a) Jihad prevents radicalism through the application of the Islamic teachings of Rahmatan Lil'alamin. b) Jihad by Optimizing Religious Dialogue in Society. c) Optimizing the Introduction and Application of Multicultural Education in society. Then, the role of religious figures, educators and parents in the multicultural jihad in the Southwest Papua region, namely: a) As educators. The role of educators is always to teach a tolerant attitude to society and provide an understanding of Islam that is rahmatan lil alamin. b) As a Motivator. Their role in providing motivation by religious and educational leaders to prevent the emergence of the seeds of radicalism in society is carried out in a variety of ways according to the needs and material to be presented. c) As Demonstrator. that teachers in the Southwest Papua region have really mastered the Islamic Religious Education material